KNOWLEDGE AND RISK OF NEEDLESTICK INJURIES IN NURSES - Wijayanti, W; Mulyani, Tri; Mintarsih, Sri (Prosiding University Research Colloquium, 2024)
Needle Stick Injury or NSI is a term for work accidents experienced by health workers caused by needle sticks or sharp medical objects that have been contaminated with infectious fluids from patients. World Health Report (2017) states that health workers are exposed to diseases due to needle stick injuries varying from 2.5% exposed to HIV, 40% exposed to Hepatitis B and Hepatitis C, while the transmission of viruses through blood borne in needle stick accidents is 30% of the Hepatitis B virus, 3% of Hepatitis C and 0.3% for the HIV virus. In RSUI Kustati Surakarta, the incidence in the last 4 years was 11 incidents. Objective: To determine the relationship between the level of knowledge and the risk of needlestick injuries in nurses. Methods: This type of research is an analytic survey with a cross sectional approach design. The study population was all functional nurses with a quota sampling technique of 55 respondents. Data analysis used Fisher Exact test. Results: good knowledge 45 respondents (81.9%) and less good 10 respondents (18.2%). Respondents at risk of NSI were 15 respondents (27.3%) and 40 respondents (72.7%) were not at risk of NSI. There is no relationship between education level and the risk of needle stick injury with Exact Sig value (2 sided) = 0.115.Conclusion: There is no relationship between the level of knowledge of nurses and the risk of needlesticks.